Anti-War Murals in Ukraine and the World During the Russian-Ukrainian War - Khudiakova, Anastasiia (HUDPROM: The Ukrainian Art and Design Journal, 2023)
At the beginning of the twenty-first century, when the Ukrainian people, realizing that they were part of the European community, defended their independence, the role of new artistic principles that corresponded to the main global trends grew significantly in the artistic and cultural sphere. New forms of artists’ appeal to the masses were becoming increasingly important in terms of social and cultural significance. Breaking away from the institutional space of museums and galleries, Action Art has taken to the streets of cities to engage in a dialogue with society. In the traditional genres of Monumental Art, there is an increasing departure from the dominant trend of imitating Soviet monumental aesthetics, which was manifested, in particular, by the spread of the muralist movement in Ukrainian cities. More and more new murals appeared on Ukrainian buildings, made both by foreign artists who were interested in Ukraine, and came here to create their murals, and by Ukrainian artists who were connected to the latest practices. However, with Russia’s attack on Ukraine on February 24, 2022, the struggle of the Ukrainian people for their freedom, democratic values, and the right to preserve and further develop their ethnicity is gaining worldwide historical significance and is widely supported around the world. In addition to the heroic resilience of the Armed Forces of Ukraine and the volunteer movement in our country, the information front plays an extremely important role. One of its cultural components is represented by contemporary anti-war murals that draw the world’s attention to the events in Ukraine, which are currently determining the future world order and the existence of humanity. Characteristically, this Ukrainian theme is widely supported by artists from many countries around the world. The murals they created are different in style, but they are united by their reference to Ukrainian symbols. This, in general, determines the relevance of this study.